Biostratigraphy and Palaeoecology of European Equus - Boulbes, Nicolas; van Asperen, Eline N. (Frontiers in Ecology and Evolution, 2019)
We present an inventory of the progress of recent research on the biostratigraphy and palaeoecology of the genus Equus sensu lato in Europe. Our discussion starts with the new hypotheses concerning the dispersal and evolution of non-caballine equids of the Early and the beginning of the Middle Pleistocene, focusing on recent discoveries, description of taxa and revised diagnosis. In particular, we deal with the major debate surrounding the number of lineages, “stenonid horses”, related species and the new subgenus “Sussemionus”. Possible phylogenetic scenarios and relationships with extant species are also taken into consideration. There is consensus that the lineage of true horses emerged in Europe at the beginning of the Middle Pleistocene. Their extensive skeletal plasticity enabled them to survive under a wide range of climatic conditions and environments, from interglacial forests to grass-steppes during glacial episodes. They exhibit homogeneous overall morphology but variability in terms of dental and skeletal proportions. Patterns of general body-size, muzzle shape, macro- and microdonty, proportions of the limbs, robustness of the metapodials and breadth of the third phalanx are influenced by global climate, the characteristics of the vegetation (in particular the degree of openness) and substrate, and are governed by Bergman’s and Allen’s rules or other environmental pressures. In addition to palaeoecological information, these ecomorphological adaptations paradoxically provide real biochronological details in a given geographical province. Throughout the Upper Pleistocene, horses underwent a size diminution initiated at the end of the Middle Pleistocene. After the Last Glacial Maximum, investigation of body-size in different regions of Europe demonstrates the existence of latitudinal and longitudinal clines, and the fragmentation of the horse population. The so-called European wild ass, Equus hydruntinus, has a wide geographical distribution but seems to be less ecologically flexible, or, alternatively, more specialized than true horses, with which it is often found in sympatry. The latest palaeogenetic studies place the species into phylogenetic context within the Asiatic wild asses, however, palaeontological evidence points to Equus hydruntinus as a separate species. Its tooth morphology varies between biogeographical areas.